Biophysical regions of the Southern Highlands, Tanzania - Joni Koskikala; Danielson R Kisanga; Niina Käyhkö (PANGAEA, 2019)
Biophysical regionalization of the Southern Highlands area of Tanzania based on open source global environmental datasets depicting climate, soil, topography and vegetation.